2021
DOI: 10.3390/ijms222413635
|View full text |Cite
|
Sign up to set email alerts
|

Targeting AVIL, a New Cytoskeleton Regulator in Glioblastoma

Abstract: Glioblastoma (GBM) is the most common adult neural malignancy and the deadliest. The standard of care is optimal, safe, cytoreductive surgery followed by combined radiation therapy and alkylating chemotherapy with temozolomide. Recurrence is common and therapeutic options in the recurrent setting are limited. The dismal prognosis of GBM has led to novel treatments being a serious roadblock in the field, with most new treatments failing to show efficacy. Targeted therapies have shown some success in many cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 70 publications
1
0
0
Order By: Relevance
“…In addition to RMS, we have found that AVIL is overexpressed in many other sarcoma types, including Ewing, synovial, osteosarcoma, and liposarcoma. These and our previous finding that AVIL plays a critical role in glioblastoma (GBM) ( 20 22 ) suggest that AVIL may be a general oncogene, not limited to a particular cancer type.…”
Section: Discussionsupporting
confidence: 64%
“…In addition to RMS, we have found that AVIL is overexpressed in many other sarcoma types, including Ewing, synovial, osteosarcoma, and liposarcoma. These and our previous finding that AVIL plays a critical role in glioblastoma (GBM) ( 20 22 ) suggest that AVIL may be a general oncogene, not limited to a particular cancer type.…”
Section: Discussionsupporting
confidence: 64%